Pharmacokinetics of immunosuppressive agents during hemoperfusion in a sheep model - Leber, Bettina; Liebchen, Uwe; Rohrhofer, Lisa; Weber, Jennifer; Klaus, Teresa; Scheier, Joerg; Sucher, Robert; Stiegler, Philipp (Frontiers in Medicine, 2023)
Hemoadsorption shows promising signals in organ preservation and post lung transplantation. However, its potential impact on the pharmacokinetics of immunosuppressant drugs (ID) is still unknown. In this interventional study CytoSorb® hemoperfusion was tested in healthy sheep (n=5) against a sham extracorporeal circuit (n=3). Seven different ID (tacrolimus (TAC), cyclosporin A (CYA), mycophenolate mofetil (MMF), everolimus (EVER), basiliximab (BAS), methylprednisolone (MP) and prednisolone (PRED)) were administered in clinically relevant doses and combinations. Their levels were measured repeatedly in blood samples from the extracorporeal circulation over six hours following administration. Population pharmacokinetic modeling analysis (NONMEM® 7.5) was performed. Negligible clearance was observed for PRED and BAS. For all other substances, a saturable adsorption sub-model with linear decrease of the adsorption effect over the adsorbed amount best described the measured concentrations. The maximum absolute adsorbed amounts (95% CI) for TAC, CYA, MMF, EVER, and MP were 0.040 (0.028 -0.053), 1.15 (0.39 -1.91), 4.17 (2.00 -6.35), 0.0163 (0.007 -0.026), and 53.4 mg (20.9 -85.9), respectively, indicating an adsorption of less than 5% of the daily administered dosages for all investigated substances. In this large animal model, CytoSorb® hemoperfusion appears to have a limited effect on the clearance of tested